Two decades of geological mapping and research in Heimefrontfjella, Dronning Maud Land, Antarctica - Weber, Klaus; Jacobs, Joachim (Polarforschung, 2009)
Heimefrontfjella is a strongly segmented NE–SW trending mountain range some 130 km long with a maximum width of about 30 km. The range takes the form of a prominent escarpment, which rises more than 1000 m above the ice plains to the northwest. The maximum elevation reaches 2700 m above sea level. Since its discovery during the German Antarctic Expedition 1938/39, very few scientists had visited Heimefrontfjella by 1985. During the mid 1960s two British geologists had visited the Heimefrontfjella and provided a geological overview of the area. Thereafter, detailed geological investigations became possible with the establishment of the Georg von Neumayer Station on the Ekström ice shelf in 1981, situated some 450 km north of Heimefrontfjella. Since then, the Georg von Neumayer Station has provided a logistical base for multidisciplinary research programs within the Atlantic sector of East Antarctica.
Keywords: Dronning Maud Land; ekspedisjoner; geologi; kartlegging

Fast-ice distribution in East Antarctica during 1997 and 1999 determined using RADARSAT data - Giles, A Barry; Massom, Robert A; Lytle, Victoria I (Journal of Geophysical Research: Oceans, 2008)
We present the first detailed maps of fast ice around East Antarctica (75°E–170°E), using an image correlation technique applied to RADARSAT ScanSAR images from November in 1997 and 1999. This method is based upon searching for, and distinguishing, correlated regions of the ice-covered ocean which remain stationary, in contrast to adjacent moving pack ice. Within the overlapping longitudinal range of ∼86°E–150.6°E, the total fast-ice area is 141,450 km2 in 1997 and 152,216 km2 in 1999. Calibrated radar backscatter data are also used to determine the distribution of two fast-ice classes based on their surface roughness characteristics. These are “smooth” fast ice (−25.4 dB to −13.5 dB) and “rough” fast ice (−13.5 dB to −2.5 dB). The former comprises ∼67% of the total area, with rough fast ice making up the remaining ∼33%. An estimate is made of fast-ice volume, on the basis of fast-ice type as a proxy measure of ice thickness and area. Results suggest that although fast ice forms 2–16% of the total November sea ice area for this sector of East Antarctica in 1997 and 1999 (average 8.3% across maps), it may comprise 6–57% of the total ice volume (average ∼28% across maps). Grounded icebergs play a key role in fast-ice distribution in all regions apart from 150°E–170°E. These are “snapshot” estimates only, and more work is required to determine longer-term spatiotemporal variability.
Keywords: Sørishavet; batymetri; biologi; havis; kartlegging; landfast is; satellite bilder; sjøis; økologi

Den Norske Antarktisekspedisjonen 1956-60 : Norway Station (Fimbul) - Henriksen, Hans-Martin (2007)
Keywords: Antarktistraktaten 1959; Den norske antarktisekspedisjonen 1956–1960; Det internasjonale geofysiske år 1957/58; Dronning Maud Land; IGY 1957-58; NAX; geologi; glasiologi; jordmagnetiske målinger; kartlegging; meteorologi; overvintring; tidevannsmålinger

Widerøe kartlegger i Antarktis - Widerøe, Turi (Perspektiv, 2007)
Keywords: Antarktis; Dronning Maud Land; Lars Christensen; Norvegia ekspedisjoner; flyhistorie; hvalfangst; kartlegging

Is, fly og skip : oppdagelse og kartlegning med fly i Øst-Antarktis 1929-1939 - Widerøe, Turi; Drivenes, Einar-Arne (Universitetet i Tromsø, 2006)
Keywords: Antarktis; ekspedisjoner; fly; fotogrammetri; geografi; historie; hvalfangst; kartlegging; kartografi; oppdagelsesreiser

Environmental aspects of the 2000/2001 Norwegian Antarctic research expedition - Njåstad, Birgit (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Antarktistraktaten; Dronning Maud Land; NARE 2000/01; avfallshåndtering; fauna; flora; forurensning; kartlegging; miljøvern

Sea ice concentration off Dronning Maud Land, Antarctica - Pavlova, Olga; Winther, Jan-Gunnar (Norsk Polarinstitutt, 2002)
This project was undertaken by the Norwegian Polar Institute for the Norwegian Petroleum Directorate (Oljedirektoratet) as support for planning of marine geophysical surveys offshore from Dronning Maud Land (DML), Antarctica. The project was carried out by scientists Olga Pavlova and Jan-Gunnar Winther at the Norwegian Polar Institute under the direction of Morten Sand at the Norwegian Petroleum Directorate. The main objectives of the project were to: a) calculate 10-day average historical (i.e., 1978-1996) sea ice concentrations off DML for the months of December through April b) identify the minimum and maximum sea ice extent occurring in the period 1978-1996 c) present the above information graphically. Daily microwave satellite data covering the period 1978-1996 with 25 x 25 km spatial resolution were used as basis for this study (see text below for description of data set).
Keywords: Dronning Maud Land; havis; kartlegging; marin geofysikk; meteorologi; sjøis

A local geoid in Dronning Maud Land - The NARE 96/97 Geoid - Eiken, Trond; Omang, Ove Christian Dahl; Øvstedal, Ola (IGeS Bulletin, 2001)
The main purpose of the present paper is to estimate the orthometric height of the Global Positioning System (GPS)-station at Troll, Dronning Maud Land, Antarctica. Located at approximately 1300 m above sea level Troll has been connected to the Geodetic Infrastructure forAntarctica (GIANT)-network, but it’s orthometric height remains undetermined. A local geoid has been determined based on gravity-, tidal- and GPS-observations and available gravity anomalies. Information about the ice-thickness has been included in the terrain model. Based on tidal measurements the mean sea level was determined in Jutulgryta, a rift zone in the Fimbulisen ice shelf. Several gravity- and GPS-stations were measured between the two points (Jutulgryta andTroll), a distance of approximately 100 km.
Keywords: Dronning Maud Land; NARE 1996/97; Troll forskningsstasjon; geodesi; kartlegging